Estudio jurídico de los informes periciales y su efecto en los procesos judiciales - Caisaguano Olmos, Darwin Enrique (2015)
The expert reports are in yes, the result of a study or analysis effected to an object in order to establish or to state the reality of a fact or juridical act, the same one that as for Law serves as way of test what he contributes to a resolution or failure of the operator of justice. The Advice of the Judicature, in his process of reform to the system of administration of justice it has implemented the Regulation of the Expert Integral System of the Judicial Function, as norm which area of application is regular the functioning and administration of the expert integral system, in relation to the qualification, designation, obligations, evaluation, training, disciplinary regime and any another aspect of the experts who take part in the judicial processes, pre procedural, or of any other nature that is carried out in the Judicial Function....